1998
DOI: 10.2337/diabetes.47.5.779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin and acipimox on VLDL1 and VLDL2 apolipoprotein B production in normal subjects.

Abstract: The objective of the study was to examine the potential differential effect of insulin and acipimox (both of which reduce free fatty acid [FFA] availability) on VLDL apolipoprotein (apo) B metabolism. We studied eight healthy men (age 40 +/- 4 years, BMI 25.8 +/- 0.9 kg/m2, plasma triglycerides 1.30 +/- 0.12 mmol/l) after an overnight fast (control study, n = 8), during inhibition of lipolysis with an antilipolytic agent, acipimox (n = 8), and under 8.5-h euglycemic-hyperinsulinemic conditions (n = 5). Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
111
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 0 publications
11
111
3
Order By: Relevance
“…Stable isotope tracers have been used in conjunction with compartmental modelling to elucidate the kinetics of apoB (a key structural protein in lipoproteins) and triglyceride across VLDL subfractions simultaneously. Adiels' model [2] has proven to be a particularly useful tool in determining how physiological features impact VLDL size and dyslipidemia [4,3,39,38]. A more in-depth model of VLDL assembly has been proposed by Shorten and Upreti [50] in which the lipid composition of secreted VLDLs can be determined from uptake of individual free fatty acids after elongation and desaturation by liver enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope tracers have been used in conjunction with compartmental modelling to elucidate the kinetics of apoB (a key structural protein in lipoproteins) and triglyceride across VLDL subfractions simultaneously. Adiels' model [2] has proven to be a particularly useful tool in determining how physiological features impact VLDL size and dyslipidemia [4,3,39,38]. A more in-depth model of VLDL assembly has been proposed by Shorten and Upreti [50] in which the lipid composition of secreted VLDLs can be determined from uptake of individual free fatty acids after elongation and desaturation by liver enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have also shown an association between liver fat content and the postprandial increase in ApoB-100 [28,29], indicating that endogenous VLDL-TAG secretion may also contribute to postprandial lipaemia in type 2 diabetes. Despite the wide range of different tracers and kinetic models employed to study VLDL-TAG kinetics, results in healthy individuals have convincingly shown that acute experimental hyperinsulinaemia decreases hepatic production of VLDL-ApoB [12,14,[30][31][32][33] and VLDL-TAG [10,12,14,30,31], primarily through suppression of VLDL 1 (rather than VLDL 2 ) production [12,32,33]. Insulin-mediated suppression of VLDL-TAG secretion may partly be attributed to diminished hepatic NEFA delivery secondary to suppression of adipose tissue lipolysis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin interacts with hepatic apoB secretion by at least two mechanisms. In healthy subjects, euglycaemic hyperinsulinaemic clamp studies have shown that insulin suppresses the production of VLDL1 particles by decreasing the availability of free fatty acids to the liver and by exerting a direct suppressive effect on apoB production [22]. In Type II diabetic subjects, euglycaemic hyperinsulinaemic clamp studies yielded contradictory results, reporting either a twofold decrease of VLDL apoB production [23], or the inability of insulin to suppress VLDL1 production despite efficient suppression of serum non-esterified fatty acids and euglycaemic conditions [24].…”
Section: Discussionmentioning
confidence: 99%